2021
DOI: 10.1177/10820132211020839
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and quality evaluation of finger millet (Eleusine coracana (L.) gaertn.) flour incorporated biscuits

Abstract: Replacing the ingredients used in biscuits with potential nutritive ingredients would be beneficial to improve the nutritional quality of the biscuits. Although, finger millet is highly nutritious when compared to other most commonly consumed cereals, limited availability of processed food products in ready-to-eat form has restricted the finger millet consumption. The present study was focused on formulating biscuits by replacing refined wheat flour with finger millet flour. Four biscuit samples were formulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In the current study, as the water holding capacity increased for flour samples F1-F6, there is a decrease in the spread ratio of the corresponding biscuit samples. A similar observation was reported by Jayawardana et al (2022) who produced biscuits by replacing wheat flour with 25%, 50%, 75% and 100% of finger millet. They reported a decreased spread ratio of biscuits from 7.56 AE 0.24 to 7.34 AE 0.20 because of the presence of high dietary fibre content in biscuits substituted with finger millet flour.…”
Section: Spread Ratio and Weight Losssupporting
confidence: 86%
See 3 more Smart Citations
“…In the current study, as the water holding capacity increased for flour samples F1-F6, there is a decrease in the spread ratio of the corresponding biscuit samples. A similar observation was reported by Jayawardana et al (2022) who produced biscuits by replacing wheat flour with 25%, 50%, 75% and 100% of finger millet. They reported a decreased spread ratio of biscuits from 7.56 AE 0.24 to 7.34 AE 0.20 because of the presence of high dietary fibre content in biscuits substituted with finger millet flour.…”
Section: Spread Ratio and Weight Losssupporting
confidence: 86%
“…A similar observation was reported by Jayawardana et al . (2022) who produced biscuits by replacing wheat flour with 25%, 50%, 75% and 100% of finger millet. They reported a decreased spread ratio of biscuits from 7.56 ± 0.24 to 7.34 ± 0.20 because of the presence of high dietary fibre content in biscuits substituted with finger millet flour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the study conducted by the Food and Agriculture Organization (FAO) in 1982 showed that substitution of wheat flour with 20 and 30% non-wheat flour for the production of bakery items leads to possible savings of 320 and 480 million dollars annually, respectively. In recent years, many studies have been conducted to determine the possible effects of the replacement of wheat flour with various cereal flours, including maize flour (Jauharah et al, 2014;Pourmohammadi et al, 2019), rice flour (Chandra et al, 2015), barley flour (Aly et al, 2021;Drakos et al, 2019;Verardo et al, 2011;Vujić et al, 2015), millet flour (Jayawardana et al, 2022;Shimray et al, 2012), oat flour (Vujić et al, 2015), and rye flour (Drakos et al, 2019). Moreover, researchers claimed that malted cereals have recently acquired popularity as a bakery ingredient due to their high polyphenol content, antioxidant activity, and structure-improving properties (Adebiyi et al, 2017;Chauhan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%